Sex differences in apoptosis do not contribute to sex differences in blood pressure or renal T cells in spontaneously hypertensive rats - Abdelbary, Mahmoud; Mohamed, Riyaz; Gillis, Ellen E.; Diaz-Sanders, Karl; Baban, Babak; Brands, Michael W.; Sullivan, Jennifer C. (Frontiers in Physiology, 2022)
Apoptosis is a physiological and anti-inflammatory form of cell death that is indispensable for normal physiology and homeostasis. Several studies have reported aberrant activation of apoptosis in various tissues at the onset of hypertension. However, the functional significance of apoptosis during essential hypertension remains largely undefined. The current study was designed to test the hypothesis that apoptosis contributes to sex differences in blood pressure and the T cell profile in spontaneously hypertensive rats (SHR). Apoptosis was measured in kidney, aorta and spleen of 13-week-old adult hypertensive male and female SHR. Female SHR had greater renal and aortic apoptosis compared to age-matched males; apoptosis in the spleen was comparable between the sexes. Based on well-established sex differences in hypertension, we tested the hypothesis that greater apoptosis in female SHR contributes to the lower BP and pro-inflammatory profile compared to males. Male and female SHR were randomized to receive vehicle or ZVAD-FMK, a cell permeable pan-caspase inhibitor, in established hypertension from 13 to 15 weeks of age or at the onset of hypertension from 6 to 12 weeks or age. Treatment with ZVAD-FMK lowered renal apoptosis in both studies, yet neither BP nor renal T cells were altered in either male or female SHR. These results suggest that apoptosis does not contribute to the control or maintenance of BP in male or female SHR or sex differences in renal T cells.